2012
DOI: 10.11606/issn.1981-0490.v15i1p65-80
|View full text |Cite
|
Sign up to set email alerts
|

A farda "siri cozido" e a "branquinha": narrativas de vida de um paciente militar alcoolista

Abstract: As narrativas de vida de um militar alcoolista, paciente de um ambulatório especializado em dependência química da Marinha do Brasil, possibilitaram a compreensão de aspectos que contribuíram para a construção de sua adição. As entrevistas revelaram a participação de processos socioculturais que influenciaram sua forma de beber, sobretudo no ambiente laboral, representados por duas categorias centrais: a farda "siri cozido" (cor alaranjada) e a "branquinha" (cachaça), relacionadas à profissão militar naval e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Consequently, the frequent relapses and the succession of misconducts related to consumption of alcohol help to provide a seal of disapproval on these individuals, a kind of stigma, quite impossible to overcome (Halpern & Leite, 2011b, 2012a. I arrived drunk on board, I was so wasted!!…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the frequent relapses and the succession of misconducts related to consumption of alcohol help to provide a seal of disapproval on these individuals, a kind of stigma, quite impossible to overcome (Halpern & Leite, 2011b, 2012a. I arrived drunk on board, I was so wasted!!…”
Section: Resultsmentioning
confidence: 99%
“…Despite probable distortions that may interfere with the results of the data collected, there will always be some bias considering that there is no absolute neutrality (Malterud, 2001). That is why the first researcher returned to CEDEQ to interview 14 patients; this is a step of the study that will be discussed in another opportunity (Halpern & Leite, 2012a, 2012b, 2014b). At a certain point of the main research, the researchers found it necessary to check the results of the ethnography and the participant observation, as well as to discuss the findings with the interviewers.…”
Section: Method Collection Process and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Apenas um artigo dos selecionados, traz a voz do sujeito como janela de compreensão dos pontos de relevância e importância do tratamento, apesar de prevalecer uma visão na sociedade moderna da dependência química como transtorno mental, importa conhecer quais vêm a ser as percepções desses sujeitos, dando relevo às experiências subjetivas relativas aos seus "processos mórbidos" (13).…”
Section: A Importância Do Tratamento Do Grupo De Reabilitação Para Osunclassified
“…Em razão de a pesquisadora ter sido Chefe e Psicóloga clínica nesse local por alguns anos, o acesso ao CEDEQ e aos pacientes foi particularmente facilitado, possibilitando o desenvolvimento das primeiras investigações científicas a respeito da dependência química nas Forças Armadas brasileiras. Perante a inexistência de dados na MB, os estudos que vêm sendo realizados no CEDEQ (Halpern e col., 2008;Halpern e col., 2010;Halpern e Leite, 2010, 2011a, 2011b, 2012a, 2012b, converteram-se em um passo singular para servir de estímulo para que outras pesquisas venham a ser empreendidas no futuro.…”
Section: Introductionunclassified